Effect of the difference enumeration attack on LowMC instances - Xinxin GE; Zhihu LI; Meiqin WANG; Kai HU (网络与信息安全学报)
The LowMC is an algorithm with low multiplicative complexities.For the parameter with limited data complexities and low number of S-boxes, the difference enumeration attack was proposed, which could theoretically attack all rounds of the LowMC.Considering that the original attack is based on the random linear layer,the strength of LowMC algorithm against differential enumeration attacks under a specific linear layer deserves more study.The difference enumeration attack cannot reach theoretical rounds through the research on the so-called key initial round.In terms of some LowMC instances, the key initial round is smaller than the theoretical value, which leads to the failure of the difference enumeration attack.Since the number of rounds of the LowMC is completely based on existing attacks, the analysis is of great significance to the rounds design of the LowMC.